2014
DOI: 10.1136/bmjopen-2013-004365
|View full text |Cite
|
Sign up to set email alerts
|

Medication use in pregnancy: a cross-sectional, multinational web-based study

Abstract: ObjectivesIntercountry comparability between studies on medication use in pregnancy is difficult due to dissimilarities in study design and methodology. This study aimed to examine patterns and factors associated with medications use in pregnancy from a multinational perspective, with emphasis on type of medication utilised and indication for use.DesignCross-sectional, web-based study performed within the period from 1 October 2011 to 29 February 2012. Uniform collection of drug utilisation data was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

39
348
10
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(425 citation statements)
references
References 41 publications
39
348
10
10
Order By: Relevance
“…Quanto ao uso de medicamentos durante a gestação, em países como França, Canadá, Estados Unidos e Brasil, foi verificado que mais de 80% das mulheres utilizam algum tipo de medicamento nesse período 13,14,15,16 , entretanto se observa uma grande variação no perfil do uso entre os países, bem como nas características maternas associadas a esse uso 15,16,17,18,19 . Alguns medicamentos recomendados para prevenção de problemas associados à gestação, incluindo ácido fólico, sulfato ferroso e vitaminas, certamente contribuem para essa alta prevalência 15 .…”
Section: Utilização De Medicamentos Antes E Durante a Gestação: Prevaunclassified
See 1 more Smart Citation
“…Quanto ao uso de medicamentos durante a gestação, em países como França, Canadá, Estados Unidos e Brasil, foi verificado que mais de 80% das mulheres utilizam algum tipo de medicamento nesse período 13,14,15,16 , entretanto se observa uma grande variação no perfil do uso entre os países, bem como nas características maternas associadas a esse uso 15,16,17,18,19 . Alguns medicamentos recomendados para prevenção de problemas associados à gestação, incluindo ácido fólico, sulfato ferroso e vitaminas, certamente contribuem para essa alta prevalência 15 .…”
Section: Utilização De Medicamentos Antes E Durante a Gestação: Prevaunclassified
“…Alguns medicamentos recomendados para prevenção de problemas associados à gestação, incluindo ácido fólico, sulfato ferroso e vitaminas, certamente contribuem para essa alta prevalência 15 .…”
Section: Utilização De Medicamentos Antes E Durante a Gestação: Prevaunclassified
“…Reports have suggested that acetaminophen is used by ∼65% to 70% of pregnant women in the United States and by ∼50% to 60% of pregnant women in western and northern Europe. 1,2 Acetaminophen crosses the placenta and can be traced in the infant's urine after prenatal exposure. 3 In 2013, researchers conducting a sibling comparison in a large, population-based Norwegian birth cohort study suggested that prenatal acetaminophen use for 28 or more days was associated with poorer motor and communicational development and externalizing problems (ie, inattentiveness and aggression) in offspring.…”
mentioning
confidence: 99%
“…Estimates of the usage prevalence of at least one prescription medication during pregnancy range from less than 30 % to over 90 % of women (3). In multinational study that collected data in years 2011-2012, 71.1 % of participating women reported use of medication during pregnancy (OTC and/or prescribed medication) in Slovenia (5). The safety of medication use during pregnancy is frequently unclear because, for the majority of medications, there is a lack of sufficient data available to fully characterise the foetal risk.…”
Section: Introductionmentioning
confidence: 99%